Optimal Incentive Contracts in the Presence of Career Concerns: Theory and Evidence - Gibbons, Robert; Murphy, Kevin J. (Journal of Political Economy, 1992)
This paper studies optimal incentive contracts when workers have career concerns–concerns about the effects of current performance on future compensation. The authors show that the optimal compensation contract optimizes total incentives: the combination of the implicit incentives from career concerns and the explicit incentives from the compensation contract. Thus, the explicit incentives from the optimal compensation contract should be strongest for workers close to retirement because career concerns are weakest for these workers. The authors find empirical support for this prediction in the relation between chief-executive compensation and stock-market performance. Copyright 1992 by University of Chicago Press.